2018
DOI: 10.4049/jimmunol.1701177
|View full text |Cite|
|
Sign up to set email alerts
|

Deficiency of the AIM2–ASC Signal Uncovers the STING-Driven Overreactive Response of Type I IFN and Reciprocal Depression of Protective IFN-γ Immunity in Mycobacterial Infection

Abstract: The nucleic acids of can be detected by intracellular DNA sensors, such as cyclic GMP-AMP synthase and absent in melanoma 2 (AIM2), which results in the release of type I IFN and the proinflammatory cytokine IL-1β. However, whether cross-talk occurs between AIM2-IL-1β and cyclic GMP-AMP synthase-type I IFN signaling upon infection in vivo is unclear. In this article, we demonstrate that mycobacterial infection of AIM2 mice reciprocally induces overreactive IFN-β and depressive IFN-γ responses, leading to highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 39 publications
3
38
0
Order By: Relevance
“…In addition, other studies have suggested that the bacterial burden does not differ between STING-deficient and WT mice, indicating that the cGAS/STING pathway is dispensable for controlling M. tuberculosis infections ( 17 , 57 ). Here, we found that M. tuberculosis MmsA can target STING for type I IFN production downregulation, which might contribute to the pathogenesis of mycobacterial infection, in accordance with previous studies ( 59 , 60 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, other studies have suggested that the bacterial burden does not differ between STING-deficient and WT mice, indicating that the cGAS/STING pathway is dispensable for controlling M. tuberculosis infections ( 17 , 57 ). Here, we found that M. tuberculosis MmsA can target STING for type I IFN production downregulation, which might contribute to the pathogenesis of mycobacterial infection, in accordance with previous studies ( 59 , 60 ).…”
Section: Discussionsupporting
confidence: 93%
“…A mycobacterial phosphodiesterase called CdnP suppresses STING activation and the type I IFN response via the hydrolysis of bacterially derived c-di-AMP and host-derived cGAMP ( 24 ). It was shown that another regulator, ASC, a key component of the inflammasome, inhibits type I IFN production by interacting with STING and disrupting its association with TBK1 via the C terminus ( 60 ). It is interesting that STING and autophagy are closely associated during M. tuberculosis infection.…”
Section: Discussionmentioning
confidence: 99%
“…Mycobacterial DNA in the host cytosol can also be sensed by absent in melanoma 2 (AIM-2) protein, which partially contributes to the activation of the NLRP3-inflammasome, promoting the maturation of the protective cytokine IL-1β ( Shah et al, 2013 ; Wassermann et al, 2015 ). This AIM-2–IL-1β signaling pathway has been recently reported to negatively regulate the STING-dependent type I IFN production in macrophages and dendritic cells (DCs) by inhibiting the association between STING and TBK1 ( Yan et al, 2018 ).…”
Section: Mechanisms Of Type I Ifn Induction In M Tuberculomentioning
confidence: 99%
“…70 In addition, during Mycobacterial infection, activated AIM2 mediated inflammasomes can interact with STING and block the activation of TBK1 and IRF3, thus inhibiting the induction of IFN-β. 71 The NLR containing protein 3 (NLRP3) has been well characterized to play important roles in viral infection and viral nucleic acid sensing. 64 However, it is unclear whether NLRP3 directly senses viral DNA or RNA.…”
Section: Inflammasomesmentioning
confidence: 99%